Progam Latihan Body Building dapat Meningkatkan Massa Otot Mahasiswa IKORA FIK UNY - Nasrulloh, Ahmad (Media Ilmu Keolahragaan Indonesia, 2012)
This study aims to determine how much influence the body building exercise program to increase muscle mass (chest, arms, thighs, and calves) FIK IKORA UNY students class of 2009. This study uses a quasi-experimental design with the one-group pretest-posttest design. The study population was IKORA student class of 2009. The sample in this study involves the entire student Prodi IKORA FIK UNY class of 2009 who took the course in the concentration of Weight Training II. The instrument used is to use a tape measure to measure centimeter meter. Analysis using normality test to determine whether the distribution of data has a normal distribution. Variant test to test the homogeneity of variance of the data similarity experimental group. T-test to determine whether there are differences in the variables between pretest and posttest in the experimental group. Results of the analysis showed that {t | t <- 2.160 or t> 2.160} with a significance level of p = 0.000 <0.05. So it can be demonstrated that significant research hypothesis: (1) body building training program can increase muscle mass chest with t test results {t = - 5.486 or 5.486}, (2) body building training program can increase muscle mass arm with the t test {t = - 7.431 or 7.431}, (3) body building exercise program can increase thigh muscle mass with the t test {t = - 2.403 or 2.403}, and (4) body building training program can increase muscle mass calf with the results of t test {t = - 2.834 or 2.834}.